Identification and Preliminary Structure-Activity Relationship Studies of 1,5-Dihydrobenzo[e][1,4]oxazepin-2(3H)-ones That Induce Differentiation of Acute Myeloid Leukemia Cells In Vitro - Laia Josa-Culleré (MDPI AG, 2021)
Acute myeloid leukemia (AML) is the most aggressive type of blood cancer, and there is a continued need for new treatments that are well tolerated and improve long-term survival rates in patients. Induction of differentiation has emerged as a promising alternative to conventional cytotoxic chemotherapy, but known agents lack efficacy in genetically distinct patient populations. Previously, we established a phenotypic screen to identify small molecules that could stimulate differentiation in a range of AML cell lines. Utilising this strategy, a 1,5-dihydrobenzo[e][1,4]oxazepin-2(3H)-one hit compound was identified. Herein, we report the hit validation in vitro, structure-activity relationship (SAR) studies and the pharmacokinetic profiles for selected compounds.